Extended-spectrum β-lactamase-producing Escherichia coli isolated from healthy humans in Mexico, including subclone ST131-B2-O25:H4-H30-Rx. (June 2017) - Cortés-Cortés, Gerardo; Lozano-Zarain, Patricia; Torres, Carmen; Alonso, Carla Andrea; Ríos-Torres, Ana María; Castañeda, Miguel; López-Pliego, Liliana; Navarro, Armando; del Carmen Rocha-Gracia, Rosa
Highlights: Detection of Escherichia coli ST131-B2-O25:H4-H30-Rx subclone in the community setting in Mexico. High carriage rate (18%) of cefotaxime-resistant E. coli among healthy humans in Puebla, Mexico. Potential spread of CTX-M-14/CTX-M-15 ESBL-producing E. coli belonging to new STs. A 140-kb conjugative IncFIA plasmid of carried the bla CTX-M-15 gene. Abstract: Objectives: The resistance mechanisms, molecular type and plasmid content of cefotaxime-resistant Escherichia coli isolated from faecal samples of healthy volunteers in Puebla, Mexico, were characterised. Methods and results: Cefotaxime-resistant E. coli were recovered from 11 (18%) of 60 healthy volunteers. The isolates (one per sample) were characterised as multidrug-resistant and phenotypically extended-spectrum β-lactamase (ESBL)-producing strains. Genes encoding resistance to β-lactams ( bla CTX-M-15, bla CTX-M-14a, bla CTX-M-14b, bla OXA-1, bla TEM-1b ), quinolones [ aac(6′)-Ib -cr, qnrB19 ], aminoglycosides [ aac(3′)-II ] and tetracycline [ tet (A), tet (B)] were detected among the 11 ESBL-producing E. coli by PCR and sequencing, as well as gene cassette arrays in class 1 ( dfrA17 – aadA5 ) and class 2 ( dfrA1 – sat2 – aadA1 ) integrons. Seven pulsotypes were identified by Xba I PFGE and the strains were distributed into phylogroups (number of isolates) A (2), B2 (4) and D (5). Seven sequence types were identified, four of them novel (ST5060, ST5079, ST5080 and ST5081), associated with phylogroups A–D. Transfer of a 140-kb IncFIA plasmid carrying the bla CTX-M-15 gene was evidenced in the ST5060 strain. Four CTX-M-15-producing E. coli strains of phylogroup B2 belonged to the ST131 complex, and IncFIB plasmids of 130 kb and 155 kb were detected in two of them. Multiple plasmid addiction systems were also found. Serotyping and fimH subtyping of ST131-B2 strains identified the ST131-B2-O25:H4-H30-Rx subclone. Additionally, this subclone and CTX-M-14-producing isolates were detected among residents living in the same household, suggesting clonal dissemination. Conclusions: This study reports the detection of E. coli ST131-B2-O25:H4-H30-Rx subclone in healthy humans in Mexico, highlighting its dissemination in the community setting.